Ø¯Ø±Ø§Ø³Ø§Øª ØªØÙ„ÙŠÙ„ÙŠØ© ÙÙŠ ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØªÙ„Ø§Ù…ÙŠØ° Ø§Ù„ØµÙÙ‘ Ø§Ù„Ø«Ø§Ù…Ù† ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„Ù†Ù…ÙˆØ°Ø¬ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø¨Ø±Ø¨ÙŠØ³ - Umam, Mustolikh Khabibul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
This research discusses the analytical study in the translation of Arabic for eighth-grade students at MTsN Model Brebes. This study is aimed to answer these research questions : 1) what are the common problems in the translation of Arabic into Indonesian in term of vocabulary for eighth-grade students at MTsN Model Brebes? . 2) how is the treatment to solve problems in the translation of Arabic into Indonesian in term of vocabulary for eighth-grade students at MTsN Model Brebes? in order to answer these questions, the researcher conducted a field study at MTsN Model Brebes. The required data was collected through testing, observation, interview, and documentary study. The researcher analyzed the data using a descriptive qualitative approach. The study resulted : 1) the students' problems in the translation of Arabic into Indonesian in term of vocabulary for eighth-grade students at MTsN Model Brebes is the lack of understanding of the application of rules and conformity of meaning. The composition of arabic sentences is different from the composition of Indonesian sentences. The students often translate from arabic into Indonesian word by word, and many of them didn't understand this way or method so they find it difficult to arrange the sentence into Indonesian. 2) and the treatment to solve problems in the translation of Arabic into Indonesian in term of vocabulary for eighth-grade students of MTsN Model Brebes is to encourage the students to memorize the vocabulary, because that is the basic to learn and master arabic, and the teacher should mention and explain the repetitively especially on the grammatical aspect. It will ease the students to understand the grammar and increasing their ability to arrange the vocabulary, and also to encourage the students to translate the arabic sentences and using them in daily conversation in term of meaning application.